Fiscal policy in the semi-structural model ECB-BASE - Krzysztof Bańkowski (European Central Bank (ECB), 2023)
Fiscal policy constitutes a key tool for business cycle stabilisation next to monetary policy. In this context, having a well-suited macroeconomic model for analysing fiscal policy at a central bank is of primary importance. This paper documents the fiscal block of the ECB-BASE, which is a semi-structural model for the euro area developed at the ECB for projections and policy analysis. The set-up of the fiscal block ensures comprehensive coverage of the government sector and tight links to the quarterly fiscal accounts. Thanks to this design, it is possible to simulate the model with a wide range of fiscal shocks, which, as shown in the paper, have distinct propagation mechanisms. Having discussed the set-up and the potency of fiscal policy in the model, this paper also includes the following applications for fiscal policy analysis: counterfactual scenarios with alternative fiscal rules, assessment of fiscal policy conducted in the euro area in the past and stochastic fiscal projections.
Keywords: C3; C5; E1; E2; E6; 330; Semi-structural model; euro area; simulations; forecasting; fiscal policy